Student–faculty interaction and academic self-concept: the intersection of race and gender. Issue 7 (10th November 2022) - Parker, Eugene T.; Trolian, Teniell L.; Stolzenberg, Ellen Bara
ABSTRACT: Using longitudinal data from the Higher Education Research Institute (HERI) at the University of California, Los Angeles, this study examined how race, gender and experiences with faculty interact and influence students' academic self-concept. Findings demonstrated a positive relationship between interactions with faculty and academic self-concept for Black, Asian and Multiracial students. Results also revealed additional notable findings about the influence of gender on academic self-concept.